2019
DOI: 10.7196/samj.2019.v109i8b.13947
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Care Society of Southern Africa Consensus Statement on ICU Triage and Rationing (ConICTri)

Abstract: GUIDELINE /SAJCCBackground. In South Africa (SA), intensive care is faced with the challenge of resource scarcity as well as an increasing demand for intensive care unit (ICU) services. ICU services are expensive, and practitioners in low-to middle-income countries experience daily the consequences of limited resources. Critically limited resources necessitate that rationing and triage (prioritisation) decisions are frequently necessary in SA, particularly in the publicly funded health sector. Purpose. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 122 publications
0
26
0
Order By: Relevance
“…The low number of O&G admissions (2.8%) is explained by the presence of a separate O&G high care; only cases requiring ventilation or dialysis are transferred to ICU. The relatively low percentage of elective admissions is a reflection of the fact that emergency admissions are often triaged over planned surgery in South Africa when there are not enough ICU beds available [11]. The elective cases who did not survive were largely complicated vascular and neurosurgical cases.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The low number of O&G admissions (2.8%) is explained by the presence of a separate O&G high care; only cases requiring ventilation or dialysis are transferred to ICU. The relatively low percentage of elective admissions is a reflection of the fact that emergency admissions are often triaged over planned surgery in South Africa when there are not enough ICU beds available [11]. The elective cases who did not survive were largely complicated vascular and neurosurgical cases.…”
Section: Plos Onementioning
confidence: 99%
“…Other reasons for demise in hospital after ICU discharge may be due to premature discharge from ICU, medical care in wards and resource limitations. There is considerable pressure on ICU beds in SA [11] and this may prompt early discharge from ICU to accommodate patients who requires organ support.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…[2,10,12] Limited available current evidence reports that SA has critical care resource shortages in terms of both numbers of beds and trained staff, resulting in limitations in the number of ICU beds available. [3,13,14] Contributing to this problem is the discrepancy between the availability of resources in the public and private healthcare systems, with only 30% of doctors working in the public sector, which serves >80% of the country's population. [13] An audit of critical care resources carried out in 2004/05 showed that 84% of private hospitals but only 23% of public hospitals have ICUs or HCAs.…”
Section: Researchmentioning
confidence: 99%
“…[3] This imbalance between demand and availability of resources in the public sector has resulted in the need for triaging of patients to prioritise ICU admission for patients who need intensive care the most. [14] International guidelines for ICU admissions in developed countries with more resources have fewer exclusionary criteria and are difficult to apply in our resource-limited setting. [15] A consensus statement to provide a framework to inform ICU admission, rationing and triage decision in an SA context was published recently.…”
Section: Researchmentioning
confidence: 99%